2000
DOI: 10.1016/s0924-7963(00)00028-2
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical modelling in the Bay of Seine (France): an improvement by introducing phosphorus in nutrient cycles

Abstract: As part of the French National Programme for Coastal Oceanography, this paper focuses on improvement of biogeochemical modelling in the Bay of Seine (Eastern Channel), by introducing phosphorus in nutrient cycles. The Bay of Seine receives the Seine river, which exhibits very high nutrient concentrations, and this coastal zone constitutes a typical case of eutrophication in a river plume area. In terms of analyses, sequential extraction and analysis of sedimentary phosphorus were used in order to measure vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
(29 reference statements)
0
32
0
Order By: Relevance
“…In the North Sea, Woodward and Owens (1990) pointed out that North Sea waters are phosphate depleted in spring, especially in waters under the influence of river inputs. More recently, Guillaud et al (2000) showed the limiting role of phosphate in the Seine plume during spring due to the decrease in phosphate in freshwater inputs over the last two decades.…”
Section: Discussionmentioning
confidence: 99%
“…In the North Sea, Woodward and Owens (1990) pointed out that North Sea waters are phosphate depleted in spring, especially in waters under the influence of river inputs. More recently, Guillaud et al (2000) showed the limiting role of phosphate in the Seine plume during spring due to the decrease in phosphate in freshwater inputs over the last two decades.…”
Section: Discussionmentioning
confidence: 99%
“…drastically change the conclusions about the controlling factor in a few years (Guillaud et al 2000). Green macrophyte blooms, on the contrary, were unanimously considered as being always nitrogen controlled.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…As the ''nutrient Ͼ phytoplankton Ͼ zooplankton Ͼ detritus'' path has been already fully described when used first in a spatial box model of the bay of Seine (Guillaud et al 2000), then in a 3D model of the same area (Cugier et al 2001;Cugier et al 2005), only the new ingredients (Ulva components) will be detailed here. An overview of the structure of the whole biogeochemical model is shown in Fig.…”
Section: Model Of the Physical Environment-the Hydrodynamical Contextmentioning
confidence: 99%
“…1), a sediment module allowing the management of sediment compartments with erosion-deposition processes (Cugier and Le Hir, 2000) and an ecological module (Cugier, 1999;Guillaud et al, 2000;Cugier et al, accepted) taking into account nutrient cycles and two phytoplankton groups, namely diatoms and nonsiliceous algae (including harmful flagellate species). Simultaneous limitation of phytoplanktonic growth by inorganic nutrient (nitrateCammonium, o-phosphate, and silica for diatoms) is taken into account by means of hyperbolic Michaelis-Menten like functions.…”
Section: The Seine Bight Modelmentioning
confidence: 99%